Neurolinguistic-based Learning Design for Madrasah Students - 'Afifah, Dinda Sayyidah; Mukmin, Mukmin; Hidayah, Nurul; Mujahid, Mujahid; Az-Zahra, Keysha Aurellia (Journal of English Language and Education, 2025)
Arabic grammar learning often faces difficulties, especially for students with a non-boarding school background who are unfamiliar with the structure of sentences and terms in Arabic. This study aims to develop Arabic grammar teaching materials in printed media using the Neurolinguistic Programming (NLP) approach to assist students in understanding Arabic rules. The method used in this study is the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The results show that the developed teaching materials received good validation from content and media experts, with scores of 84.76 and 84.61, respectively. The trial on students showed significant improvement, with the average pre-test score of 44 and post-test score of 68.33, and paired t-test results indicated a Sig. value of 0.000, signifying a significant change. The effectiveness of the teaching materials was also supported by a N-Gain Score of 0.4493, indicating moderate effectiveness. The student satisfaction score reached 79.23%, indicating that students were satisfied with the NLP-based teaching materials. However, improvements in material aspects and presentation methods are still needed to meet optimal competency standards.